PENGARUH STRATEGI PEMBELAJARAN INQUIRI MELALUI KEGIATAN MENANAM KECAMBAH TERHADAP KEMAMPUAN SAINS ANAK USIA 5-6 TAHUN DI TK ANASTASIA DELI SERDANG - Indah Manda Sari Telaumbanua; Mei Lyna Girsang (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini (PGPAUD), 2022)
The purpose of this study was to determine the effect of Inquiry Learning Strategy through Planting Sprouts on Science Ability of 5-6 Years Old Children at Anastasia Deli Serdang Kindergarten. The sample in this study was children class B2 totaling 20 people. This research is an experimental research with a Pre-experimental One Group Pretest and Posttest Design. The sampling technique used was purposive sampling. The data of the study were analyzed statistically by using SPSS 22 with the formula mean, median, mode, Shapiro-Wilk normality test, one-sample t- test. Based on the results of the study, it was found that the average score of children's science abilities in the pretest was 8 with a percentage of 50% while after the treatment or posttest it increased with an average score of 11 with a percentage of 70%. The results of t count > t table then Ha is accepted and Ho is rejected (value 27,053 > 2,093) and a significant value of 0.23 > 0.05. So it can be concluded that there is an Influence of Inquiry Learning Strategy through Planting Sprouts Activities on the Science Ability of Children 5 - 6 Years Old at Anastasia Deli Serdang Kindergarten